Symbolic and functional brand effects in the hedonic assessment of South African wines - D. Priilaid; P. Van Rensburg (South African Journal of Business Management, 2010)
Proceeding from work that identifies price as an extrinsic cue that can mediate between a wine's perceived and intrinsic merit, the brand construct is presented as an additional potential mediator. Here we define (1) "functional" brands as representations of intrinsic (blind-tasted) quality, and (2) "symbolic" brands (as proxied by the difference between a wine's intrinsic and extrinsic (sighted-tasted) evaluations) as placebos. Using a database of 8225 paired tastings (sighted and blind) of popular South African cultivars sampled over an eight year period, we control for contending price and vintage cues to identify the scale, character and distribution of a given set of functional and symbolic brand effects. Respectively these are identified as occurring in the frequency of roughly two-to-one. The 30 strongest of each are tabled. A subset of brands that present simultaneously as both functional and symbolic is further scrutinised. This set decomposes into two distinctive clusters located approximately one standard deviation left and right of the broader intrinsic mean. The smaller Zone of Symbolic Values is characterised by weak intrinsics and strong positive placebos. The second, larger Zone of Functional Values presents the opposite: negative placebos and strong functional intrinsics. Through the calibration and scaling of these brand-effects, wine producers can better understand what proportion of their product's sight-driven appeal can ably be ascribed to a brand's placebo as opposed to the underlying quality. Consequently their marketers may now more knowledgably amplify (or, where appropriate, down-play) the label-cue and adjust their wine marketing communication accordingly.
Keywords: 650